Hubungan Antara Usia Awal Menikah Dengan Gambaran Hasil Pemeriksaan Pap Smear - Agustina Mar’atus Sholichah; ,Dian Sukmawati (2020)
Cervical cancer is one of the most common types of malignancy in the cervix. This case is found in many developing countries, include in Indonesia. The incidence of cervical cancer in Indonesia is still needs prevention. If cervical cancer found early, it can be given therapy immediately so the recovery level can be maximized. Women with young sexual intercourse age are at risk for cervical cancer. The purpose of this study is to find out the relationship between the age of marriage and the pap smear test results. This research used an analytical observational using cross sectional design to find the relationship between the age of married with the pap smear test in 200 respondents in PMB Dian Sukmawati, SST., M.Kes. The results showed that respondents who were married at < 20 years old mostly had IIIrd grade on pap smear test results of 48 respondents (24%), respondents who were married at age 20-35 mostly had grade II pap smear examination results of 44 respondents (22%), while respondents who were married at the age of >35 years mostly had the results of grade I pap smear examinations which were as many as 4 respondents (2%). Chi Square analysis found p value 0.002 (< 0.05). It can be concluded that there is a relationship between the age of marriage and the pap smear test results.